2017
DOI: 10.1016/j.nicl.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional network changes and cognitive control in schizophrenia

Abstract: Cognitive control is a cognitive and neural mechanism that contributes to managing the complex demands of day-to-day life. Studies have suggested that functional impairments in cognitive control associated brain circuitry contribute to a broad range of higher cognitive deficits in schizophrenia. To examine this issue, we assessed functional connectivity networks in healthy adults and individuals with schizophrenia performing tasks from two distinct cognitive domains that varied in demands for cognitive control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 75 publications
5
37
1
Order By: Relevance
“…In other words, the DPX was most modular (Q) and contained the greatest mutual information (I) whereas RiSE encoding was least modular (Q) and contained the least amount of mutual information (I). Incorporating the current findings with previous studies investigating FPN specific functional connectivity changes associated with cognitive control on the same sample (Ray et al (2017), the DPX task displayed the greatest change in within FPN functional connectivity between high and low CC conditions (Ray et al, 2017) and our current work suggests it is also most modular (i.e. greatest network segregation) and experiences the least amount of network reorganization.…”
Section: Network Reorganizationsupporting
confidence: 73%
See 4 more Smart Citations
“…In other words, the DPX was most modular (Q) and contained the greatest mutual information (I) whereas RiSE encoding was least modular (Q) and contained the least amount of mutual information (I). Incorporating the current findings with previous studies investigating FPN specific functional connectivity changes associated with cognitive control on the same sample (Ray et al (2017), the DPX task displayed the greatest change in within FPN functional connectivity between high and low CC conditions (Ray et al, 2017) and our current work suggests it is also most modular (i.e. greatest network segregation) and experiences the least amount of network reorganization.…”
Section: Network Reorganizationsupporting
confidence: 73%
“…Previous fMRI whole-brain analyses from our group using a different healthy sample have shown that contrasting B-cues relative to A-cues in the DPX task elicits widespread activations in the cognitive control FPN, including bilateral DLPFC, bilateral fusiform gyri, and right inferior parietal gyrus (Lopez-Garcia et al, 2015). These activation findings have been replicated in the current sample (Poppe et al, 2016) and subsequent functional connectivity analyses have also demonstrated network specific engagement of the FPN during the DPX task (Ray et al, 2017).…”
Section: Data Acquisitionsupporting
confidence: 73%
See 3 more Smart Citations